Training on cervical cancer and HPV vaccine for 9-13 years’ adolescent girls - Yemane, Tesfalem Tilahun (PT. Riset Press International, 2024)
This community service project aimed to raise awareness about cervical cancer and the importance of the HPV vaccine for 9-13-year-old girls and their parents. The training was designed to address the knowledge gap regarding cervical cancer and HPV vaccine among 9-13-year-old girls and their parents, we can empower them to make informed decisions about vaccination. Before the implementation of training, a community survey was conducted. The findings of the survey helped us to identify gaps in knowledge and attitudes and inform the development of training as an intervention. Through training & distributed training materials the outcome of the community service was achieved. The knowledge of school adolescent girls was evaluated and improved. The uptake of HPV vaccination was increased and all unvaccinated school girls were vaccinated after training. Training participants were empowered to correct any misconceptions within the community. Hopefully, this community service provide input for others to adopt and apply in other similar schools.